When speculation matters - Robles, Miguel; Torero, Máximo; von Braun, Joachim (International Food Policy Research Institute, 2009)
The food price crisis of 2007–08 had several causes—rising demand for food, the change in the food equation through biofuels, climate change, high oil prices—but there is substantial evidence that the crisis was made worse by the malfunctioning of world grain markets. Dozens of countries imposed restrictions on grain exports that resulted in significant price increases, given the thinness of markets for major cereals. A number of countries adopted retail price controls, creating perverse incentives for producers. Speculative price spikes built up, and the gap between spot and futures prices widened, stimulating overregulation and trader policing in some countries and causing some commodity exchanges in Africa and Asia to halt grain futures trading. Some food aid donors defaulted on food aid contracts. The World Food Programme (WFP) had difficulty getting access to enough grain quickly for its humanitarian operations. Developing countries began urgently rebuilding their national stocks and reexamining the “merits” of self-sufficiency policies for food security. These reactions began as consequences, not causes, of the price crisis, but they exacerbated the crisis and increased the risks posed by high prices. By creating a positive feedback loop with high food prices, they took on a life of their own, increasing price levels and price volatility even more, with adverse consequences for the poor and for long-term incentives for agricultural production. Because they impeded the free flow of food to where it is most needed and the free flow of price signals to farmers, these market failures imposed enormous efficiency losses on the global food system, hitting the poorest countries hardest. Changes in supply and demand fundamentals cannot fully explain the recent drastic increase in food prices. Rising expectations, speculation, hoarding, and hysteria also played a role in the increasing level and volatility of food prices. The flow of speculative capital from financial investors into agricultural commodity markets has been drastic, and the number of future traded contracts is increasing over time. From May 2007 to May 2008, the volume of globally traded grain futures and options rose significantly. Excessive speculation in the commodity futures market could, in principle, push up futures prices and— through arbitrage opportunities—spot prices above levels justified by supply and demand fundamentals. The supposed impact of speculation is sometimes confused, however, with the impact of hedging, which reflects consumers’ genuine concerns about future fundamentals and desire to hedge against risks. This brief analyzes the role of financial speculation in the behavior of agricultural prices in recent years.